TEACHER’S ROLE IN TEACHING ENGLISH AS A FOREIGN LANGUAGE - R., Suhartina (JURNAL ILMU BUDAYA, 2015)
The teaching of English as a foreign language in Indonesia aims at providing learners with adequate knowledge touse the language for communicative purposes, both oral and written form. Although student-centered learning hasbeen the dominant activities in the classroom during this decade, the roles of English teachers in managing the class,in applying teaching and learning methods, as well as in preparing the learning materialsare still of crucial partsespecially in cunducting multidirectional communication between teacher and students and among the studentsthemselves.In term of teaching, teachers are not only requested to transfer knowledge from their brain to their students‘, but alsoprepare them with adeqateskills and valuable social norms for the use of conducting good relationship in social life.This article attempts to investigate the roles teachers that should be performed at class and then give some advice ofaffective strategies in English teaching as a foreign language.Keywords: English Foreign Language, Teachers‘ role, Communicatice competence